2020
DOI: 10.29333/ejmste/7950
|View full text |Cite
|
Sign up to set email alerts
|

Addition Concept through the Lenses of Young Children: Creating Visual Representation with Digital Cameras

Abstract: Acquiring abstract Mathematics concepts is often challenging for young children. This study explored young children's use of digital cameras to exhibit their understanding of the addition concept. It investigated how the processes involved in producing the photographs and creating the visual representation that helped to develop the children's comprehension of the concept of addition. This study employed a qualitative research design and data collection included observation, dialogues with children and childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In this way, children can see the problems they are trying to solve as a process which is easier to understand. This is a more engaging way for children to learn because it helps them connect the numbers to the corresponding words (Abu Bakar et al, 2020b). In addition to this, the visual and tactile nature of representations can be useful for helping children practice problem solving.…”
Section: Problem Statemetmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, children can see the problems they are trying to solve as a process which is easier to understand. This is a more engaging way for children to learn because it helps them connect the numbers to the corresponding words (Abu Bakar et al, 2020b). In addition to this, the visual and tactile nature of representations can be useful for helping children practice problem solving.…”
Section: Problem Statemetmentioning
confidence: 99%
“…In a study on solving addition operation problems among six-year-old children, Abu Bakar et al (2020b) found that children face difficulties and it is difficult to translate the addition operation in writing mathematical sentences that use the symbol plus (+) and equal to (=) or in other words is writing arithmetic equations because children are not yet able to express relationships between two objects involved in a problem solving addition operation.…”
Section: Problem Solvingmentioning
confidence: 99%
“…As a research tool, photography permits children to express their views, thinking and understanding without being restricted to their verbal and written language competencies (Bakar, Yunus, Mohamed, & Karim, 2020). This is specifically beneficial for young children who frequently struggle to communicate with others about what they have in mind due to having limited language proficiencies.…”
Section: Introductionmentioning
confidence: 99%